Integrating zakat into Indonesian fiscal sytem in the light of siyasah shar‘Iyyah - Nashr, Akbar; Kayadibi, Saim (2012)
Nowadays, the idea of integrating zakat into fiscal system has arisen in Muslim countries including Indonesia. It is argued that zakat, in history, has played a significant role to create welfare among societies. It is proven at the time of Caliph ‘Umar ibn ‘Abdul ‘Aziz that zakat has alleviated poverty at that time alongside tax. Having considered such achievement, some scholars argued that zakat should be reintegrated into current fiscal system. This paper, therefore, attempts to study the feasibility of integrating zakat into Indonesian fiscal system. Employing descriptive analysis based on Siyasah Shar‘iyyah (high objectives of the Shari‘ah). Therefore, the objectives of the study are set with these following points: 1) to address the strength and the weakness of the implementation of this idea, 2) to assess its opportunity as well as its threat, 3) to examine whether the integration of zakat will secure maslahah (benefit) or create mafsadah (harm). The research will determine whether the integration of zakat into current fiscal system is in line with the Siyasah Shar‘iyyah or not. Keywords: Zakat; Fiscal; Integration; SWOT analysis; Siyasah shar‘iyyah, Contemporary fiqh.